Feasibility of Class XII Enzyme and Cell Metabolism Material Booklet Media Based on Acute Toxicity Test of Zuriat Fruit Seed Extract - Ariesta Albriyanti; Ruqiah Ganda Putri Panjaitan; Hayatul Fajri; Dai Yixuan (Universitas Pendidikan Indonesia, 2024)
Learning media is a tool that makes it easier for educators to convey material to students effectively and efficiently to improve the quality of learning. Biology subjects in the essential enzymes and cell metabolism competencies require precision and accuracy, so appropriate learning media are needed. Booklets are a medium that can make it easier for students to learn. They are small, attractive, practical, simple, and easy to carry anywhere. This research aims to determine the suitability of booklet media for enzyme material and cell metabolism based on the acute toxicity test of Zuriat seed extract. This research's stages are determining potential problems, collecting information, designing booklets, validating booklets, revising booklets, and making booklets. The initial stage of making the booklet is to carry out an acute toxicity test of Zuriat seed extract and design the contents of the booklet. The suitability of the booklet is seen from the assessment carried out by five validators. The research instrument uses a validation sheet. The aspects assessed include format, content, and language. The research results show that the booklet can be declared suitable as a learning medium. The value for the format, content, and language aspects is 1. The results of the validation show the CVI value is 1. It can be concluded that the class XII booklet on enzymes and cell metabolism is based on the acute toxicity test Zuriat seed extract as a learning medium, which can be declared feasible.